Predicting Fatigue Crack Growth Behavior of Coalesced Cracks Using the Global-Local Superimposed Technique (Fracture and Structural Integrity, 2022)
The S-version Finite Element Method (FEM) is known as a global-local superimposed approach that consists of two separate meshes referred to as global and local cracks. The relationship between the energy release rate and the Stress Intensity Factor (SIF) is evaluated to characterize the growth behavior of the fatigue cracks. The SIF is determined using the Virtual Crack Closure Method (VCCM). The cracks propagated in the direction of the loading before coalescing into a single crack. Each crack begins with a length of 10mm and a depth of 3mm. After the crack coalesces, the diameter of the surface crack before it breaks is 28mm, whereas the depth of the crack is 5.3mm. The V-shaped surface crack forms quickly after coalescence occurs and continues to propagate into a massive semi-elliptical surface crack before finally breaking. The result was validated and compared between S-version FEM and the analytical solution. The behavior of the fatigue crack growth shows a good agreement between both methods with small errors. The result indicates that the Root Mean Square Error (RMSE) values before coalescing are 0.1496 with 0.6, and after coalescing is 0.4, the RMSE value is 0.1665. Therefore, it can be stated that the S-version FEM approach can predict the growth of fatigue cracks.
Keywords: S-version FEM; Coalesced cracks; Fatigue crack growth behaviour